Analisis Strategi Peningkatan Penerimaan Pajak Kendaraan Bermotor Pada Samsat Kota Sibolga - Dian Ananda Putri; Imsar Imsar (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
Motor Vehicle Tax (PKB), is a regional tax levied on ownership of motorized vehicles, both two-wheeled and four-wheeled, is one of the levies that makes a significant contribution to regional income growth. The operational legal basis for the strategy for implementing Motor Vehicle Tax (PKB) collection in Sibolga City is contained in the regional regulations themselves which are the basis for implementing PKB in a particular area. The aim of this research is to evaluate and ensure the best course of action for Sibolga Samsat motor vehicle tax recipients. A qualitative descriptive analysis approach was used in this research. Field observation and interview methods were used in the data collection procedures. The research findings show that the method used by the Sibolga Regional Samsat Office has had a very beneficial impact in increasing motor vehicle taxes because thanks to the programs and strategies implemented, the public can easily find out about changes to the tax payment system. . Results of interviews with agency leaders; He also explained the tactics used at the Sibolga City Samsat office. According to him, the Regional Revenue Agency decided to carry out this outreach because policy changes often occur in the field of taxation, especially regarding motor vehicle tax. Therefore, socialization is needed so that policy changes are more easily understood by the wider community. Two supporting factors, namely human resources and facilities and infrastructure, have an impact on Sibolga City's plan to increase the number of motor vehicle tax recipients. This inability to integrate with the community is what prevents this technique from being successful.